2017
DOI: 10.1093/jpepsy/jsx052
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Hygiene and Sleep Outcomes in a Sample of Urban Children With and Without Asthma

Abstract: Considering urban stressors when treating pediatric populations is important, as factors related to urban stress may influence sleep hygiene practices and sleep outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Results indicated children with higher levels of depressive and somatic symptoms tended to have more inconsistent sleep duration across monitored nights. Consistent with previous research, urban risk factors including neighborhood risk and poverty level were associated with more variability in sleep duration, 10 which may be related to inconsistent or poor sleep hygiene behaviors (eg, inconsistent bedtimes and waketimes). In addition to urban risk factors, internalizing symptoms such as depressive and somatic symptoms may also challenge implementing healthy sleep behaviors consistently (eg, a consistent bedtime routine and consistent sleep schedule) and should be further explored in the context of specific sleep hygiene behaviors.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Results indicated children with higher levels of depressive and somatic symptoms tended to have more inconsistent sleep duration across monitored nights. Consistent with previous research, urban risk factors including neighborhood risk and poverty level were associated with more variability in sleep duration, 10 which may be related to inconsistent or poor sleep hygiene behaviors (eg, inconsistent bedtimes and waketimes). In addition to urban risk factors, internalizing symptoms such as depressive and somatic symptoms may also challenge implementing healthy sleep behaviors consistently (eg, a consistent bedtime routine and consistent sleep schedule) and should be further explored in the context of specific sleep hygiene behaviors.…”
Section: Discussionsupporting
confidence: 88%
“…8 Environmental conditions more prevalent in low-SES, urban areas (eg, increased noise during the night, uncomfortable bed, and uncomfortable room temperatures) have been linked to inconsistent and later sleep onset times, wake times, and daytime sleepiness, 9 as well a shorter and more variable sleep duration. 10 Other stressors more likely in urban environments, such as witnessing violence, have also been associated with adolescent self-reported sleep problems such as difficulties falling asleep and daytime sleepiness. 8 Studies focusing on sleep in ethnic minority children have found that compared to non-Latino white (NLW) children, ethnic minority children experienced shorter sleep duration 11 and more daytime sleepiness.…”
Section: Sleep Outcomes In Urban Minority Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Youth with asthma and obesity experience increased respiratory symptoms and have decreased response to inhaled corticosteroids compared to youth with asthma with healthy body weight [ 3 ]. Inflammation, a key physiological factor seen in both asthma and obesity, has been linked to fatigue and poor sleep patterns [ 16 , 25 , 26 , 27 , 28 , 29 ], resulting in difficulty maintaining cognitive focus in school [ 26 , 30 ]. Additionally, exercise intolerance and dyspnea can be triggers for youth with asthma and obesity, as they can cause or mimic symptoms of dyspnea, often resulting in activity avoidance [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%